Beyond sleep: A multidimensional model of chronotype. (May 2023) - Chauhan, Satyam; Norbury, Ray; Faßbender, Kaja Christina; Ettinger, Ulrich; Kumari, Veena
Abstract: Chronotype can be defined as an expression or proxy for circadian rhythms of varied mechanisms, for example in body temperature, cortisol secretion, cognitive functions, eating and sleeping patterns. It is influenced by a range of internal (e.g., genetics) and external factors (e.g., light exposure), and has implications for health and well-being. Here, we present a critical review and synthesis of existing models of chronotype. Our observations reveal that most existing models and, as a consequence, associated measures of chronotype have focused solely or primarily on the sleep dimension, and typically have not incorporated social and environmental influences on chronotype. We propose a multidimensional model of chronotype, integrating individual (biological and psychological), environmental and social factors that appear to interact to determine an individual's true chronotype with potential feedback loops between these factors. This model could be beneficial not only from a basic science perspective but also in the context of understanding health and clinical implications of certain chronotypes as well as designing preventive and therapeutic approaches for related illnesses. Highlights: Chronotype is influenced by a range of internal and external factors. Existing models of chronotype have focused primarily on the sleep dimension. Here, we propose a model, integrating individual, environmental and social factors. This model could be useful in addressing negative outcomes of certain chronotype/s.